Reclusión mayor y pena pecuniaria en los delitos ambientales. - Espinoza Ludeña, Loyda Yolanda (2013)
Through research it has been shown that it is essential to have a criminal framework both objective and substantive guesses the need that warrants the reality of the crime rate in the environment, establish more rigorous penology the phenomenon of environmental crime.